Modélisation de réseaux écologiques et impacts des choix méthodologiques sur leur configuration spatiale : analyse de cas en Estrie (Québec, Canada) - Amélie Bernier (Éditions en environnement VertigO, 2013)
Ecological networks are designed to maintain biodiversity and ecological processes by protecting habitats and their connectivity. Several approaches can be used to define the components of these networks at each stage of their design. These choices are a major source of uncertainty that influence the spatial configuration of the networks obtained, but they have not been extensively studied. In this study, several methods were applied to the steps for selecting core areas and designing corridors for the same territory in the Eastern Townships, Quebec. The aim of the study was to design an ecological network suitable for an indicator species, the Pileated Woodpecker (Dryocopus pileatus). Two methods for selecting core areas were tested : a multi-criteria analysis and a habitat suitability index. These two methods, which were also used in the step for creating matrices of resistance to movement, were combined with three methods to design corridors : least-cost path, least-cost corridor, and circuit theory. Six ecological networks were created and compared. The results show considerable differences in the spatial configuration of the networks, whether in terms of the area and perimeter of different elements or the corridor width. These results are discussed in relation to two limiting factors for these methodological steps, which are data availability and the representativeness of the models. We also provide suggestions to help decision makers facing the many possible scenarios for ecological networks.